Female figures on the Torana - Temples of India Project Team (Jio Institute, 2024)
The shaft of the torana (ornamental gateway) displays four figures on each of its four sides of the octagonal base, while the remaining four sides are left plain. Each side of the shaft features three female figures and one male figure. One of the female figures is shown standing, holding a bowl and from her other hand, she gracefully holds her drapery. The figure embodies feminine beauty, characterized by her curvaceous figure, elegant hairdo, and jewellery.